Effect of Processing Level on Metabolite Profiles and Antioxidant Activity of Palm Sugar Using Untargeted LC–MS - Arif Rizkika Putra; Tuty Anggraini; Fauzan Azima (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2026)
Palm sugar derived from sugar palm sap (Arenga pinnata Merr.) is widely used as a natural sweetener and contains various minor compounds that may contribute to its functional properties. Differences in processing intensity during the production of liquid, molded, and granulated palm sugar may induce chemical transformations affecting metabolite composition and antioxidant activity. However, comparative information linking processing level with these changes remains limited. This study evaluated the effects of different processing levels on the chemical characteristics and DPPH radical scavenging activity of palm sugar products. Antioxidant activity was determined using the DPPH method at a concentration of 1000 ppm, while metabolite profiling was conducted using untargeted LC–MS/MS Q-TOF in positive ion mode over an m/z range of 50–1200. Untargeted LC–MS/MS combined with principal component analysis (PCA) indicated differences in metabolite profiles among products, with liquid palm sugar showing the highest number of tentatively annotated features, followed by molded and granulated palm sugar. Increasing processing intensity was associated with shifts in metabolite composition, including reduced occurrence of oligosaccharide-related compounds and tentative detection of monosaccharide-related and heat-derived compounds such as maltol and phenolic-type derivatives. DPPH radical scavenging activity increased with processing level, reaching 39.23%, 55.93%, and 63.76% for liquid, molded, and granulated palm sugar, respectively. These findings suggest that thermal processing modifies the chemical profile of palm sugar and may improve its antioxidant-related properties under the conditions studied. Contribution to Sustainable Development Goals (SDGs):SDG 3: Good Health and Well-beingSDG 9: Industry, Innovation and InfrastructureSDG 12: Responsible Consumption and Production